Загрузил kochedykova2014

алгебра 1

Реклама
√𝟑
√𝟑
y
√𝟑
-𝟑
-1
−√𝟑
√𝟑
𝟑
𝝅
𝟐
1
𝝅
𝟒
√𝟐
𝟐
𝟓𝝅
𝟔
𝝅
𝟔
√𝟑
−
𝟐
√𝟐
−
𝟐
cost
sint
tgt
ctgt
𝟕𝝅
𝟔
̶
+
̶
̶
II
−
𝟏
𝟐
cost
sint
tgt
ctgt
I
III
IV
𝟏
𝟐
̶
̶
+
+
м
−
𝟓𝝅
𝟒
𝟏
𝟐
−
√𝟐
𝟐
−
√𝟑
𝟐
𝟒𝝅
𝟑
ось sin
𝟑𝝅
𝟐
x
√𝟑
−
𝟐
+
̶
̶
̶
√𝟑
-𝟑
𝟕𝝅
𝟔
̶
+
̶
̶
√𝟐
−
𝟐
cost
sint
tgt
ctgt
𝟏𝟏𝝅
𝟔
−
𝟏
𝟐
-1
I
III
IV
cost
sint
tgt
ctgt
𝟏
𝟐
̶
̶
+
+
м
−
𝟏
𝟐
−
√𝟐
𝟐
−
√𝟑
𝟐
𝟒𝝅
𝟑
ось sin
−√𝟑
𝝅
𝟔
II
𝟓𝝅
𝟒
𝟕𝝅
𝟒
𝟓𝝅
𝟑
cost
sint
tgt
ctgt
𝟑𝝅
𝟐
√𝟑
𝝅
𝟒
√𝟐
𝟐
𝟏
𝟐
ось cos
√𝟑
𝟐
1
𝝅
𝟑
√𝟑
𝟐
𝟓𝝅
𝟔
+
+
+
+
√𝟐
𝟐
cost
sint
tgt
ctgt
√𝟑
𝟑
√𝟑
𝟑
𝝅
𝟐
𝟑𝝅
𝟒
𝟏
𝟐
ось cos
-1
−√𝟑
𝟐𝝅
𝟑
√𝟑
𝟐
𝟑𝝅
𝟒
cost
sint
tgt
ctgt
√𝟑
𝝅
𝟑
𝟐𝝅
𝟑
y
√𝟑
-𝟑
+
+
+
+
√𝟐
𝟐
cost
sint
tgt
ctgt
√𝟑
𝟑
x
√𝟑
𝟐
+
̶
̶
̶
𝟏𝟏𝝅
𝟔
√𝟑
-𝟑
𝟕𝝅
𝟒
𝟓𝝅
𝟑
-1
−√𝟑
0
sin t
1
cos t
0
tg t
0
ctg t
-
0
sin t
1
cos t
0
tg t
0
ctg t
-
0
sin t
1
cos t
0
tg t
0
ctg t
-
𝝅
𝟔
30˚
√𝟑
𝟐
𝟏
𝟐
√𝟑
𝟑
√𝟑
𝝅
𝟔
30˚
√𝟑
𝟐
𝟏
𝟐
√𝟑
𝟑
√𝟑
𝝅
𝟔
30˚
√𝟑
𝟐
𝟏
𝟐
√𝟑
𝟑
√𝟑
𝝅
𝟒
45 ˚
√𝟐
𝟐
√𝟐
𝟐
1
1
𝝅
𝟑
60 ˚
𝟏
𝟐
√𝟑
𝟐
√𝟑
√𝟑
𝟑
𝝅
𝟐
90 ˚
0
1
-0
𝝅
𝟒
45 ˚
√𝟐
𝟐
√𝟐
𝟐
1
𝝅
𝟑
60 ˚
𝟏
𝟐
√𝟑
𝟐
√𝟑
𝝅
𝟐
90 ˚
0
1
√𝟑
𝟑
0
𝝅
𝟒
45 ˚
√𝟐
𝟐
√𝟐
𝟐
1
𝝅
𝟑
60 ˚
𝟏
𝟐
√𝟑
𝟐
√𝟑
𝝅
𝟐
90 ˚
0
1
√𝟑
𝟑
0
1
--
1
--
𝟐𝝅
𝟑
120
𝟏
−
𝟐
√𝟑
𝟐
−√𝟑
−
√𝟑
𝟑
𝟐𝝅
𝟑
120
𝟏
−
𝟐
√𝟑
𝟐
−√𝟑
−
√𝟑
𝟑
𝟐𝝅
𝟑
120
𝟏
−
𝟐
√𝟑
𝟐
−√𝟑
−
√𝟑
𝟑
𝟑𝝅
𝟒
135
√𝟐
−
𝟐
√𝟐
𝟐
-1
-1
𝟑𝝅
𝟒
135
√𝟐
−
𝟐
√𝟐
𝟐
-1
-1
𝟑𝝅
𝟒
135
√𝟐
−
𝟐
√𝟐
𝟐
-1
-1
𝟓𝝅
𝟔
150
√𝟑
𝟐
𝟏
𝟐
√𝟑
−
𝟑
−√𝟑
Аргумент t
𝟕𝝅
𝝅
𝟔
180
210
-1
√𝟑
−
𝟐
𝟏
0
−
𝟐
0
√𝟑
𝟑
-√𝟑
Аргумент t
𝟕𝝅
𝟓𝝅
𝝅
𝟔
𝟔
150
180
210
-1
√𝟑
√𝟑
−
𝟐
𝟐
𝟏
𝟏
0
−
𝟐
𝟐
0
√𝟑
√𝟑
−
𝟑
𝟑
-−√𝟑
√𝟑
𝟓𝝅
𝟔
150
√𝟑
𝟐
𝟏
𝟐
√𝟑
−
𝟑
−√𝟑
Аргумент t
𝟕𝝅
𝝅
𝟔
180
210
-1
√𝟑
−
𝟐
𝟏
0
−
𝟐
0
√𝟑
𝟑
-√𝟑
𝟓𝝅
𝟒
225
√𝟐
−
𝟐
√𝟐
−
𝟐
1
1
𝟒𝝅
𝟑
240
𝟏
−
𝟐
√𝟑
−
𝟐
√𝟑
𝟑𝝅
𝟐
270
0
-1
--
√𝟑
𝟑
0
𝟓𝝅
𝟒
225
√𝟐
−
𝟐
√𝟐
−
𝟐
1
𝟒𝝅
𝟑
240
𝟏
−
𝟐
√𝟑
−
𝟐
√𝟑
𝟑𝝅
𝟐
270
0
1
√𝟑
𝟑
0
𝟓𝝅
𝟒
225
√𝟐
−
𝟐
√𝟐
−
𝟐
1
𝟒𝝅
𝟑
240
𝟏
−
𝟐
√𝟑
−
𝟐
√𝟑
𝟑𝝅
𝟐
270
0
1
√𝟑
𝟑
0
𝟓𝝅
𝟑
300
𝟏
𝟐
√𝟑
−
𝟐
√𝟑
−
√𝟑
𝟑
𝟕𝝅
𝟒
315
√𝟐
𝟐
√𝟐
−
𝟐
-1
-1
𝟏𝟏𝝅
𝟔
330
√𝟑
𝟐
𝟏
−
𝟐
√𝟑
−
𝟑
−√𝟑
𝟐𝝅
360
1
0
0
--
sin2t + cos2t = 1
tgt =
ctg =
𝑠𝑖𝑛𝑡
tgt • ctgt = 1
1
tg2t + 1 =
𝑐𝑜𝑠2𝑡
1
ctg2t + 1 =
2
-1
--
-1
--
−
√𝟑
𝟑
𝟓𝝅
𝟑
300
𝟏
𝟐
√𝟑
−
𝟐
√𝟑
−
√𝟑
𝟑
𝑠𝑖𝑛2𝑡
2
sin t + cos t = 1
tgt =
𝟓𝝅
𝟑
300
𝟏
𝟐
√𝟑
−
𝟐
√𝟑
𝑠𝑖𝑛𝑡
𝑐𝑜𝑠𝑡
𝑐𝑜𝑠𝑡
𝟕𝝅
𝟒
315
√𝟐
𝟐
√𝟐
−
𝟐
-1
-1
𝟏𝟏𝝅
𝟔
330
√𝟑
𝟐
𝟏
−
𝟐
√𝟑
𝟑
−√𝟑
−
𝟐𝝅
360
1
0
ctg =
𝑠𝑖𝑛𝑡
tgt • ctgt = 1
1
tg2t + 1 =
𝑐𝑜𝑠2𝑡
1
ctg2t + 1 =
0
--
-1
𝟏𝟏𝝅
𝟔
330
√𝟑
𝟐
𝟏
−
𝟐
√𝟑
−
𝟑
−√𝟑
𝟐𝝅
360
1
0
0
--
𝑠𝑖𝑛2𝑡
sin2t + cos2t = 1
tgt =
𝟕𝝅
𝟒
315
√𝟐
𝟐
√𝟐
−
𝟐
-1
𝑠𝑖𝑛𝑡
𝑐𝑜𝑠𝑡
𝑐𝑜𝑠𝑡
𝑠𝑖𝑛𝑡
𝑐𝑜𝑠𝑡
𝑐𝑜𝑠𝑡
ctg =
𝑠𝑖𝑛𝑡
tgt • ctgt = 1
1
tg2t + 1 =
𝑐𝑜𝑠2𝑡
1
ctg2t + 1 =
𝑠𝑖𝑛2𝑡
Скачать